Surfactant-assisted solid-state synthesis of 6LiMn0.8Fe0.2PO4·Li3V2(PO4)3/C nanocomposite for lithium-ion batteries. Issue 44 (23rd May 2017) - Wang, Yanming; Zhu, Bo; Liu, Xiaoyu; Wang, Fei
Abstract : The nanosized 6LiMn0.8 Fe0.2 PO4 ·Li3 V2 (PO4 )3 /C nanoparticles were synthesized by a facile surfactant-assisted solid-state method, exhibiting outstanding rate capability and cycling stability. Abstract : Herein, nanosized LiMnPO4 /C, LiMn0.8 Fe0.2 PO4 /C, and 6LiMn0.8 Fe0.2 PO4 ·Li3 V2 (PO4 )3 /C cathode materials were synthesized by a facile surfactant-assisted solid-state method. Lauric acid was used as a surfactant and carbon source to fabricate the carbon-coated nanoparticles. The phase compositions and elemental distribution of 6LiMn0.8 Fe0.2 PO4 ·Li3 V2 (PO4 )3 /C were analyzed via X-ray diffraction and energy dispersive spectroscopy. Due to the unique heterogeneous nanostructure, 6LiMn0.8 Fe0.2 PO4 ·Li3 V2 (PO4 )3 /C exhibits superior electrochemical performance as compared to the individual LiMn0.8 Fe0.2 PO4 /C and LiMnPO4 /C. The composite cathode delivers large discharge capacities of 162 and 167 mA h g −1 at 0.1C in the voltage range of 2.0–4.5 V and 2.0–4.8 V, respectively, along with good rate capability and long cycle life.